2021
DOI: 10.1021/acs.jpcc.1c05887
|View full text |Cite
|
Sign up to set email alerts
|

Underpotential Deposition of Silver on Gold for Surface Catalysis of Plasmon-Enhanced Reduction of 4-Nitrothiophenol

Abstract: Underpotential deposition (UPD) in electrochemistry can be used to form heterometal deposits on substrates at a monolayer level, altering the surface characteristics. In this work, we demonstrated the application of UPD metals in catalyzing photoreactions of adsorbed molecules under the excitation of surface plasmons. For a monolayer of 4-nitrothiophenol (4-NTP) on a roughened Au substrate, the reduction and dimerization to 4,4′-dimercaptoazobenzene (DMAB) were monitored under conditions of Ag UPD using electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The optical system in Fig. 2(d) can be used not only for EC-TERS, but also for various other measurements, such as TERS in air, 33) surface-enhanced Raman spectroscopy (SERS), 34) STM luminescence in air using tunnel current as the excitation source, 35) and, fluorescence. 36) The results of EC-TERS measurements on a benzenethiol monolayer, which has been used as a standard sample in studies of ambient TERS, 37) are shown in Fig.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…The optical system in Fig. 2(d) can be used not only for EC-TERS, but also for various other measurements, such as TERS in air, 33) surface-enhanced Raman spectroscopy (SERS), 34) STM luminescence in air using tunnel current as the excitation source, 35) and, fluorescence. 36) The results of EC-TERS measurements on a benzenethiol monolayer, which has been used as a standard sample in studies of ambient TERS, 37) are shown in Fig.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…46 The vibrational modes of DMAB are 1151 cm À1 and correspond to bC-H + CN, 44 and the other important modes are 1393 cm À1 (dCH+ nCC), 1442 cm À1 (-NQN-), 1571 cm À1 (C-C stretching of ring, nCC). [47][48][49] At high concentration, the molecules are crowded, i.e., are close together on the surface of the nanoparticle. Therefore, they have the propensity to form DMAB.…”
Section: Sers-based Operando Spectroscopy For Probing Light-driven Su...mentioning
confidence: 99%
“…Alternation of the electronic structure of the molecule−electrode interface through UPD has been utilized for modulating the adsorption affinity of a molecule, 33−35 heterogeneous catalytic properties, 36−38 and plasmonic properties. 39 Recently, UPD-based bimetallic electrodes were employed to enhance the electrical conductance of junctions. 40,41 Gu et al 40 Here we show how the UPD-based bimetallic electrode (BE) affects the thermopower of self-assembled monolayer (SAM)-based junctions (Figure 1a).…”
mentioning
confidence: 99%
“…This technique offers a potent means of creating bimetallic materials and investigating the impact of the adlayer of the second metal. Alternation of the electronic structure of the molecule–electrode interface through UPD has been utilized for modulating the adsorption affinity of a molecule, heterogeneous catalytic properties, and plasmonic properties . Recently, UPD-based bimetallic electrodes were employed to enhance the electrical conductance of junctions. , Gu et al observed improved conductance of α,ω-alkanoic acids by modifying the bare gold electrode with UPD adlayers of silver or copper.…”
mentioning
confidence: 99%